Musical journeys : performing migration in twentieth-century music - Scheding, Florian, 1976- (Martlesham : The Boydell Press, 2019)
The displacement of European musics and musicians is a defining feature of twentieth-century music history.
Introduction: Mobility between margin and centre -- Angels in Paris -- Facing the nation -- Airwaves in London -- Singing exile of progress and nostalgia -- Jewish memories.
Includes bibliographical references (pages 165-185) and index.
Print version record.
JSTOR
Keywords: Music -- 20th century -- History and criticism; Emigration and immigration; Émigration et immigration; Migration period (Medieval culture or period); emigration; migrations (events); immigration; MUSIC -- History & Criticism; Emigration and immigration; Music; 1900-1999; Criticism, interpretation, etc